Organic substrates in Calycophyllum spruceanum (Benth.) plants Production - Abanto-Rodriguez, Carlos (2016)
This work was to evaluate the influence of the organic compound in the production of plants capirona. The experiment was conducted at the Research Center Dale E. Bandy the IIAP Ucayali. Treatments were distributed in a randomized complete (DCA) design with 5 treatments 3 replications and 10 plants per experimental unit, the treatments were: T1 [alluvial soil]; T2 [agricultural soil]; T3 [alluvial soil + agricultural soil (1: 1)]; T4 [alluvial soil + rice hull + chicken manure (1: 1: 1)] and T5 [agricultural soil + rice hull + chicken manure (1: 1: 1]. The variables evaluated at the end of the experiment were plant height (H) (cm), basal diameter (BD) (mm), number of leaves, relative height and basal diameter (H/BD), dry mass of the aerial part (DMAP) (g) dry weight of the root (DWR) (g) and quality index Dickson (QID). The results show that the T4 and T5 treatments, had higher significant differences in all variables evaluated in relation to other treatments. In that sense it is concluded that the substrates [alluvial soil + rice hull chicken manure] and [agricultural soil + rice hull + chicken manure], waste from animal and vegetable sources provided greater efficiency and better quality growth of plants capirona suitable for definitive field.